Geopolitical risk contagion across strategic sectors: Nonlinear evidence from defense, cybersecurity, energy, and raw materials - Catalin Gheorghe; Oana Panazan (PLoS ONE, 2025)
This study investigates the effect of geopolitical risk on the market volatility of four strategic sectors − defense, cybersecurity, energy, and critical raw materials − using a sample of 90 companies and ETFs over the 2014–2025 period. Applying Quantile-on-Quantile Connectedness (QQC) and Causality-in-Quantiles (CiQ) methods, the study captures the asymmetric and nonlinear relationships between geopolitical uncertainty and market volatility. The findings show that defense and cybersecurity sectors act as defensive assets during geopolitical crises, while energy and critical raw materials sectors exhibit increased sensitivity to external shocks. The QQC approach reveals heightened interconnectedness under extreme volatility, while CiQ tests confirm regime-dependent causal links. These differences across sectors provide a comprehensive perspective on geopolitical contagion and offer actionable insights for policymakers and investors seeking to develop more resilient strategies in volatile global conditions.